2021
DOI: 10.1186/s43066-021-00120-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mental health and anxiety level among hepatitis C patients during COVID-19 pandemic in Pakistan

Abstract: Background This study was conducted to check anxiety level and mental stress in the 200 confirmed hepatitis C patients during the COVID-19 pandemic. The Chinese version of the Beck Anxiety Inventory (BAI) score index was used to measure the anxiety level of HCV-positive patients. BAI score index of different demographic factors such as gender, age, occupation, and education of all the sampled population was calculated. Results The highest BAI score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…A study conducted among Pakistani medical workers has found that the fear of COVID-19 causes a high level of anxiety among medical personnel and patients with hepatitis. This study shows that the promotion of stable mental health plays an important role in boosting the immune system, and further demands the need for positive steps to be taken to reduce such epidemics and anxiety among medical workers (Rafique et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…A study conducted among Pakistani medical workers has found that the fear of COVID-19 causes a high level of anxiety among medical personnel and patients with hepatitis. This study shows that the promotion of stable mental health plays an important role in boosting the immune system, and further demands the need for positive steps to be taken to reduce such epidemics and anxiety among medical workers (Rafique et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…57 Psychological distress is also often observed in people living with chronic HCV, the diagnosis of which can be a major stressful event resulting in significant psychological and emotional burden, even in the absence of significant liver disease. 58 Other factors such as the negative social impact of living with HCV and viewing HCV as a ‘deadly disease’ further contribute to this distress, while a recent study from Rafique et al 59 concluded that PLHCV experienced increased anxiety and stress during the COVID-19 pandemic. Research also suggests stigma associated with genital herpes infection contributes to the adverse psychological consequences that stem from this otherwise relatively medically innocuous viral infection, and psychological distress has even been prospectively linked to recurrence frequency in genital herpes.…”
Section: Discussionmentioning
confidence: 99%